2023
DOI: 10.18203/2394-6040.ijcmph20230245
|View full text |Cite
|
Sign up to set email alerts
|

Modified B. G. Prasad socioeconomic scale: 2022 update of India

Abstract: Socioeconomic status (SES) is one of the most important determinants of family’s health as well as access to resources. It is vital to determine the SES of the participant in community-based research for documenting the incidence and prevalence of numerous health related events. The modified BG Prasad SES is one of the most widely used tool to determine the SES of rural and urban population but this scale requires regular update taking into account the inflation and deflation of value of the Rupees as this sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The difference in the prevalence of depression in the different occupational groups was not significant. In reference to socioeconomic class (Modified B G Prasad Classification) 9 , higher prevalence of depression was seen in Class IV (43.9%) and Class V (28.0%) socioeconomic status followed by those belonging to Class III (25.6%) and Class II socioeconomic status (22.5%). It is seen that the lower socioeconomic status has higher prevalence of depression.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The difference in the prevalence of depression in the different occupational groups was not significant. In reference to socioeconomic class (Modified B G Prasad Classification) 9 , higher prevalence of depression was seen in Class IV (43.9%) and Class V (28.0%) socioeconomic status followed by those belonging to Class III (25.6%) and Class II socioeconomic status (22.5%). It is seen that the lower socioeconomic status has higher prevalence of depression.…”
Section: Resultsmentioning
confidence: 96%
“…Various studies have revealed that the prevalence rates for depression in the community samples of the elderly in India varied from 6% to 58%. 8,[9][10][11] Sampling strategies, sample sizes, study setting, and instruments used in different studies may be the factors for this varied prevalence .We also tried to look for association of depression with a number of factors such as age group, education, occupation, socioeconomic status, type of family and various comorbidities and disabilities with depression.…”
Section: Discussionmentioning
confidence: 99%
“…Prasad Scale, updated January 2022 (77.1%). 20 Maximum participants were from phase 1 MBBS (28.6%). About 14.4% had any addiction; of whom tobacco (57.6%) was the most commonly used addictive substance found among 35 students followed by alcohol 19 (30.5%) (Table 1).…”
Section: Resultsmentioning
confidence: 98%
“…Smartphone usage (assessed using digital well-being and parental control application in smartphone) and mindfulness (assessed using MAAS) 19 were taken as dependent variables, while independent variables were sociodemographic variables (age in completed years, gender, level of education, socioeconomic status as per Modified B G Prasad Scale 2022, 20 type of family, and total number of family members), addiction history, and presence of comorbidities.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…Nutrition : Dietary data are being collected by the 24-hour dietary recall, multiple pass method over 2 days – one weekday and one weekend day (Saturday or Sunday). This enables us to observe trends in dietary patterns, food security, and the influence of climate change (parents & children) (44) (objective 3).…”
Section: Methodsmentioning
confidence: 99%